2014
DOI: 10.1021/am507087p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Modification of Aramid Fibers by Bio-Inspired Poly(dopamine) and Epoxy Functionalized Silane Grafting

Abstract: A novel biomimetic surface modification method for meta-aramid (MPIA) fibers and the improvement on adhesion with rubber matrix was demonstrated. Inspired by the composition of adhesive proteins in mussels, we used dopamine (DOPA) self-polymerization to form thin, surface-adherent poly(dopamine) (PDA) films onto the surface of MPIA fibers simply by immersing MPIA fibers in a dopamine solution at room temperature. An epoxy functionalized silane (KH560) grafting was then carried out on the surface of the poly(do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
195
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(203 citation statements)
references
References 32 publications
8
195
0
Order By: Relevance
“…More importantly, the resultant polydopamine (PDA) film can act as a platform for easy and diverse secondary reactions to immobilize different functional groups [28][29][30][31][32][33]. It affords an opportunity to create a facial and versatile pathway for surface functionalization of PP.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the resultant polydopamine (PDA) film can act as a platform for easy and diverse secondary reactions to immobilize different functional groups [28][29][30][31][32][33]. It affords an opportunity to create a facial and versatile pathway for surface functionalization of PP.…”
Section: Introductionmentioning
confidence: 99%
“…This film can be adhered onto the surfaces of almost all materials with no exception of superhydrophobic materials with low surface energy [27][28][29]. Therefore, dopamine has been used to modify the surface of various textile materials, e.g., polyester (PET) fabrics [30], carbon fiber [31] and aramid fibers [32] to improve the adhesive strength between coatings and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Coating the reinforcing fibers with sizing agents is an alternating way to improve interface structure. [22][23][24][25][26][27] de Lange and coworkers developed an "adhesion activation" method by coating an epoxy-amine finish (diglycidyl ether of glycerol as epoxy and piperazine as amine, at a mass ratio of 9: 1) onto the fiber surface, which remarkably enhanced the interfacial adhesion. [22][23][24] Tian and coworkers introduced the epoxy group onto the aramid fiber surface by…”
mentioning
confidence: 99%
“…27 Due to the strong interaction between epoxy groups and the rubber matrix, the singlefiber pull-out tests showed that the interfacial adhesion increased by 62.5%.…”
mentioning
confidence: 99%